Toward a service-based workflow for automated information extraction from herbarium specimens. (8th October 2018) - Kirchhoff, Agnes; Bügel, Ulrich; Santamaria, Eduard; Reimeier, Fabian; Röpert, Dominik; Tebbje, Alexander; Güntsch, Anton; Chaves, Fernando; Steinke, Karl-Heinz; Berendsohn, Walter
Abstract: Over the past years, herbarium collections worldwide have started to digitize millions of specimens on an industrial scale. Although the imaging costs are steadily falling, capturing the accompanying label information is still predominantly done manually and develops into the principal cost factor. In order to streamline the process of capturing herbarium specimen metadata, we specified a formal extensible workflow integrating a wide range of automated specimen image analysis services. We implemented the workflow on the basis of OpenRefine together with a plugin for handling service calls and responses. The evolving system presently covers the generation of optical character recognition (OCR) from specimen images, the identification of regions of interest in images and the extraction of meaningful information items from OCR. These implementations were developed as part of the Deutsche Forschungsgemeinschaft-funded a standardised and optimised process for data acquisition from digital images of herbarium specimens (StanDAP-Herb) Project.